High-Tech Worship? Using Presentational Technologies Wisely - Schultze, Quentin J. (Quentin James) (Michigan Baker Books, 2004)
Increasing numbers of churches today use high-tech tools such as videos and PowerPoint presentations in their worship services. But without wisdom, those tools can turn their services more into entertainment than worship. How can churches use technology
Keywords: Public worship -- Audio-visual aids